Pentingnya Minum Air Putih Bagi Kesehatan Tubuh Pada Siswa - Teduh Purnama; Iin Anindia Oktaviyani; Chalisa Destiana Margaretha; Aprilia Indah Kusuma Wardani; Liss Dyah Dewi A (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Drinking, especially water, is very important for the health of the body. In Indonesia, there are 22 percent of children still minimally in drinking water. Elementary school students are busy studying and playing so children often forget to drink. Although drinking water is very important because it can maintain the physical and mental health of students, not being able to drink water every day can cause short-term and long-term illness. The purpose of this study was to find out the importance of drinking water for the health of elementary school students. This research is qualitative descriptive research with a field research design. Sampling was carried out by Random Sampling, with a sample of 104 respondents. Most respondents based on most class V as many as 39 respondents (40.8%), based on gender most of them are female as many as 57 respondents (40.8%), and most teenagers in 3 districts namely Sleman, Kota and Bantul based on students' attitudes in drinking water as many as 50 respondents (40.8%) are categorized as adequate. The habit of elementary school students drinking water every day can be improved by education carried out by the school and the participation of parents. So as to increase the knowledge and attitude of students in drinking water.